The use of nanoscale fluorescence microscopic to decipher cell wall modifications during fungal penetration - Ellinger, Dorothea; Voigt, Christian A. (Frontiers in Plant Science, 2014)
Plant diseases are one of the most studied subjects in the field of plant science due to their impact on crop yield and food security. Our increased understanding of plant–pathogen interactions was mainly driven by the development of new techniques that facilitated analyses on a subcellular and molecular level. The development of labeling technologies, which allowed the visualization and localization of cellular structures and proteins in live cell imaging, promoted the use of fluorescence and laser-scanning microscopy in the field of plant–pathogen interactions. Recent advances in new microscopic technologies opened their application in plant science and in the investigation of plant diseases. In this regard, in planta Förster/Fluorescence resonance energy transfer has demonstrated to facilitate the measurement of protein-protein interactions within the living tissue, supporting the analysis of regulatory pathways involved in plant immunity and putative host-pathogen interactions on a nanoscale level. Localization microscopy, an emerging, non-invasive microscopic technology, will allow investigations with a nanoscale resolution leading to new possibilities in the understanding of molecular processes.